Institution-wide and Within-Patient Evolution of Daptomycin Susceptibility in Vancomycin-Resistant Enterococcus faecium Bloodstream Infections. (14th January 2018) - Woods, Robert J.; Patel, Twisha S.; Nagel, Jerod L.; Newton, Duane W.; Read, Andrew F.
Abstract : We report daptomycin minimum inhibitory concentrations (MICs) for vancomycin-resistant Enterococcus faecium isolated from bloodstream infections over a 4-year period. The daptomycin MIC increased over time hospital-wide for initial isolates and increased over time within patients, culminating in 40% of patients having daptomycin-nonsusceptible isolates in the final year of the study. Infect Control Hosp Epidemiol 2018;39:226–228